Zdravotně technické a plynovodní instalace v objektu střední školy - Bobrovský, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Diplomová práce se zabývá možnými způsoby návrhu přípravy teplé vody a spotřebou teplé vody v objektu školy. V teoretické části je shrnuta základní teorie týkající se ohřevu teplé vody. Jsou zde popsány dnes užívané způsoby přípravy teplé vody a zásady návrhu rozvodu teplé vody po objektu. Ve druhé části diplomové práce je popsáno měření spotřeby teplé vody na objektu školy a statistické vyhodnocení naměřených údajů. Konec kapitoly je věnován návrhu systému ohřevu teplé na zadaném objektu s využitím dat získaných z měření. Jedna varianta návrhu byla vybrána a použita do 3. části, kde je řešený projekt zdravotně technických a plynovodních instalací v objektu střední školy. V závěru je technické řešení objektu popsáno v technické zprávě.

The diploma thesis deals with possible ways of designing hot water preparation and hot water consumption in a school building. The theoretical part summarizes the basic theory related to hot water heating. It describes the methods of hot water preparation used today and the design principles of hot water distribution in the building. In the second part of the thesis, the measurement of hot water consumption on the object of a primary school and the statistical evaluation of the measured data are described. The end of the chapter is devoted to the design of a hot water heating system on the specified object using the data obtained from the measurements. One variant of the design was selected and used in Part 3, where the design of the sanitary and gas installations in the secondary school building is addressed. Finally, the technical design of the building is described in the technical report.
The Sanitary and Gas Instalation in the High School
Keywords: Ohřev teplé vody; střední škola; způsoby přípravy teplé vody; průtokový ohřev; měření spotřeby teplé vody. Křivka odběru teplé vody; Hot water heating; secondary school; methods of hot water preparation; instantaneous water heater; measurement of hot water consumption. Hot water consumption curve